Quality of the design of removable partial dentures in working models - Calzada-Gonzales, Nancy (2019)
The main aim of the study was to determine the quality of the design of Removable Partial Dentures in 2017 Huánuco working models based on the years of experience of the professionals.  Descriptive study, basic and prospective transversal type. With a quantitative approach, 280 working models for the preparation of removable partial dentures were included in the study. Samples were collected in the dental laboratories of the city of Huánuco. The components of the RPD design were observed at each sample. Descriptive statistics were applied. The results found 73 (91.3 %) did not make a system of design (instructions from the dental professional about the design that the RPD should have) delegating the design choice to the dental laboratory technician and a smaller percentage followed the instructions for the elaboration of the RPD 7 (8.8 %), from which 51 (63.8 %) were superior dental arches and a smaller percentage of them were the inferior dental arches 29 (36.3 %). The design quality of the removable partial denture base in working models, whose design was acceptable to 46 (67.5 %). It is concluded that the design quality of the removable partial dentures in a high percentage is designed incorrectly, the components used do not meet ideal requirements. 22.86 % of the dentists send the working models with system of design for the fabrication of the removable partial dentures.